2019
DOI: 10.1037/ccp0000434
|View full text |Cite
|
Sign up to set email alerts
|

Applying lessons from task sharing in global mental health to the opioid crisis.

Abstract: The current opioid crisis in the United States has been considered an "epidemic of poor access to care." Similar to the shortage of trained providers to prescribe medications to treat opioid use disorder (OUD), there is a severe shortage of trained providers to meet the mental health needs of patients with OUD. These workforce shortages are evident nationwide, yet are particularly salient in rural areas. In this commentary in response to the article "Integrating Addiction Medicine into Rural Primary Care: Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In many health/behavioral interventions in low-resource settings including South Africa, task-sharing-training lay health workers to safely deliver care that has traditionally been delivered by specialists-is essential (Magidson et al, 2019a(Magidson et al, , 2019c(Magidson et al, , 2017b. Our prior work has demonstrated that HIV/AOD patients perceive an intervention task-shared to peerspeople with similar lived experiences to be less stigmatizing (Magidson et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…In many health/behavioral interventions in low-resource settings including South Africa, task-sharing-training lay health workers to safely deliver care that has traditionally been delivered by specialists-is essential (Magidson et al, 2019a(Magidson et al, , 2019c(Magidson et al, , 2017b. Our prior work has demonstrated that HIV/AOD patients perceive an intervention task-shared to peerspeople with similar lived experiences to be less stigmatizing (Magidson et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there must be increased support and resources for clinicians in rural areas who prescribe buprenorphine for MOUD. This may be done through the creation of a clinician collaboration network for experienced buprenorphine prescribers to share insight and education with new prescribers [ 30 ], increased education and staff support for primary care clinicians [ 35 ], implementation of lay healthcare workers, and task sharing into treatment plans [ 45 ], and utilization of community pharmacies as a point of access to care in rural communities as an added layer of support [ 46 , 47 ]. We also suggest the consideration of incentives that will increase the level of provider participation, including but not limited to decreased prescriber regulations (i.e., prior authorization requirements) and increased reimbursements for services provided.…”
Section: Reviewmentioning
confidence: 99%
“…As has been highlighted, we know that LHWs can be trained to deliver EBPs with fidelity from efforts in LMICs (Barnett, Gonzlez, et al, 2018;Singla et al, 2017); however, their roles in the U.S. may impact adoption of these interventions. For example, it has been noted that peer providers in the U.S. typically focus more on sharing lived experiences and providing support, with more formal interventions being seen as outside of the scope of their job description (Magidson et al, 2019). Relatedly, the systems they work within will impact if they have the job flexibility, supervision, and support to adopt EBPs.…”
Section: Adoption: What Leads Lhws To Adopt Ebps?mentioning
confidence: 99%
“…LHWs have identified a need for training and supervision to support their work with families and communities (Klein et al, 2020). In LHW models of care, implementation is often overseen or evaluated by clinical psychologists, who provide training and ongoing supervision Magidson et al, 2019). At the same time, psychologists providing training or supervision need to engage in cultural humility and embrace the importance of shared knowledge and skills (Mundeva et al, 2018).…”
Section: Implementation: Which Implementation Supports Do Lhws Need?mentioning
confidence: 99%